The implementation of a guided inquiry model assisted by visual media to improve students learning outcomes on digestive system learning materials - Marisa Cantika Putri; Martini Martini (Jurnal Pijar Mipa, 2022)
This research aimed to determine the influence and the effectiveness of the guided inquiry model assisted by visual media to improve students' learning outcomes. This research used a one-group pretest-posttest design. The research subject is 12 class VIII students in one public Junior High School in Sidoarjo. The instrument and data collection techniques are pretest-posttest. The data analysis techniques were learning implementation analysis and learning outcomes analysis using the Wilcoxon test and normalized gain score. The results showed that the percentage of the learning implementation for the first and second meetings was very good. The average N-Gain score was 0,60, which was in the medium category. Based on this result, it can be concluded that the guided inquiry model assisted by visual media can improve students' learning outcomes.